Antimicrobial activity of Azadirachta indica and Moringa oleifera extracts against some pathogenic bacteria isolated from urinary tract infections - Ameer Faraj Taha (Tikrit Journal of Pure Science)
Bacterial resistance to antibiotics poses a serious challenge to clinicians and the pharmaceutical industry. Efforts are ongoing to counteract this issue, including extensive screening of medicinal plants from traditional medicine systems to find safer and more effective antimicrobial agents. This study involved collecting 120 clinical urine samples from patients aged 10-60 years with urinary tract infections (UTIs) at Kirkuk Hospital between December 2023 and April 2024. Bacterial isolates were identified using microscopy, morphological analysis, and biochemical tests. Agar diffusion tests were performed to evaluate antimicrobial activity. Results indicated that E. coli was the most prevalent bacterium (45.9%), followed by S. aureus (20.3%), K. pneumonia (14.9%), P. aeruginosa (10.8%), and P. mirabilis (8.1%). E. coli, K. pneumonia, and P. aeruginosa showed 100% resistance to Ampicillin, while all studied bacteria were highly sensitive to Imipenem and Amikacin. Extracts of Azadirachta indica and Moringa oleifera demonstrated significant antibacterial activity, with inhibition zones varying based on concentration. At 100 mg/mL, A. indica and M. oleifera showed inhibition diameters ranging from 20.6 mm to 38.3 mm against different bacterial isolates.